Scientific Realism and International Relations
X, 258 p.
Keywords: Critical and scientific realism have emerged as important perspectives on international relations in recent years. The attraction of these approaches lies in the claim that they can transcend the positivism vs postpositivism divide. This book demonstrates the vitality of this approach and the difference that 'realism' makes.